Prognostic genes related to mitochondrial dynamics and mitophagy in diffuse large B-cell lymphoma are identified and validated using an integrated analysis of bulk and single-cell RNA sequencing - Chen, Qingjiao; Chen, Mingui; Wang, Jizhen; Dong, Jinfeng; Yang, Apeng; Zhu, Xiaolin; Lin, Qiaoxian; Huang, Jinlong; Lai, Guilan; Zheng, Meihong; Zeng, Zhiyong; Chen, Junmin; et al. (Frontiers in Immunology, 2025)
BackgroundWhile the link between mitochondrial homeostasis, specifically dynamics and mitophagy, and the progression of diffuse large B-cell lymphoma (DLBCL) has been suggested, their prognostic significance and functional networks remain unclear. This study aimed to investigate the role of mitochondrial dynamics-related genes (MDRGs) in DLBCL patient outcomes.MethodsCandidate MDGRs were identified via Weighted Gene Co-expression Network Analysis (WGCNA) and differential expression analysis using public RNA-seq data. A prognostic signature was established via LASSO-Cox regression, followed by proportional hazards assumption validation. Functional pathways, regulatory networks (including miR-1252-5p/NEAT1), and a risk-scoring model were analyzed. Model assessment included nomograms, immune cell infiltration, m6A regulator, and pharmacogenomics. Single-cell mapping was employed to characterize B-cell differentiation and spatial gene expression. Finally, the findings were validated using RT-qPCR on clinical samples.ResultsSix lysosomal-enriched genes (TCF7, CEBPA, BBC3, GALR3, BMP8B, and BAALC) were identified as independent prognostic indicators. A composite model integrating our risk score and clinical parameters showed superior predictive accuracy (AUC > 0.8). High-risk DLBCL was characterized by altered M0 macrophage infiltration, YTHDC1-mediated m6A dysregulation, and dihydrotestosterone sensitivity. Single-cell analysis revealed an association between stage-specific B-cell differentiation and gene expression gradients. RT-qPCR confirmed the upregulation of CEBPA, BBC3, GALR3, BMP8B, and BAALC in DLBCL clinical samples.ConclusionTCF7, CEBPA, BBC3, GALR3, BMP8B, and BAALC were identified as novel lysosomal pathway-enriched prognostic genes in DLBCL. Our validated composite model demonstrated strong predictive power. These findings establish an association between high-risk disease and specific tumor microenvironment alterations (M0 macrophages), epitranscriptomic dysregulation (m6A), and therapeutic vulnerabilities, providing valuable insights for refining prognosis and advancing targeted therapies for DLBCL.